2017
DOI: 10.1016/j.molbiopara.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The Plasmodium alveolin IMC1a is stabilised by its terminal cysteine motifs and facilitates sporozoite morphogenesis and infectivity in a dose-dependent manner

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Plasmodium encodes only eight alveolins with nonredundant roles at specific life cycle stages. Careful dissection of these proteins in Plasmodium berghei has shown that the composition of the SPN has a stage-specific role in maintaining the tensile strength of the parasite, as well as a role in morphology [60,85,87,92]. In both T. gondii and Sarcocystis, IMC proteins undergo a dynamic and hierarchical assembly throughout both endodyogeny and the life cycle [11,16].…”
Section: Stress-resistant Scaffoldingmentioning
confidence: 99%
“…Plasmodium encodes only eight alveolins with nonredundant roles at specific life cycle stages. Careful dissection of these proteins in Plasmodium berghei has shown that the composition of the SPN has a stage-specific role in maintaining the tensile strength of the parasite, as well as a role in morphology [60,85,87,92]. In both T. gondii and Sarcocystis, IMC proteins undergo a dynamic and hierarchical assembly throughout both endodyogeny and the life cycle [11,16].…”
Section: Stress-resistant Scaffoldingmentioning
confidence: 99%
“…These observations indicate that IMC1h without its non-alveolin module causes an intermediate phenotype with regards to sporozoite morphogenesis. Interestingly, mutations of putative amino- or carboxy-terminal palmitoylation sites of the sporozoite-specific alveolin IMC1a have also been shown to affect sporozoite shape and size, being in between that of null mutant and wildtype sporozoites (Al-Khattaf et al, 2017). Collectively, these findings point to a fundamental role of the alveolins in determining sporozoite size and shape.…”
Section: Discussionmentioning
confidence: 99%
“…2 and Text S1 to S7 ), and in some cases (e.g., Symbiodinium [ Text S5.24 ], Guillardia [ Text S4.43 ], and Toxoplasma [ Text S1.45 ]) they are abundant. Mutagenesis of the C residues in the IMC1c protein of Plasmodium affects sporozoite shape and infectivity ( 62 ), and the residues have been shown to undergo palmitoylation ( 173 ), possibly contributing to membrane associations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the only intermediate-filament proteins reported to form a membrane skeleton are the nuclear lamins ( 59 ). Therefore, referring to epiplastins as intermediate filaments or intermediate filament-like ( 24 , 27 , 32 , 36 , 51 , 60 62 ) can be misleading. Rather, the epiplastins represent a novel protein class that proves to be restricted, with a few interesting exceptions, to lineages that assemble epiplasts, a restriction that may be informative in assigning evolutionary relationships between various taxa.…”
Section: Introductionmentioning
confidence: 99%